Political Participation by the Deprived: A Comparative Analysis in Political Behavior by Unemployed Young Adults - Bassoli, Matteo; Lahusen, Christian (Partecipazione e conflitto, 2015)
Research within the social sciences has argued recurrently that unemployment has a negative impact on political participation, particularly long-term joblessness. One of the milestones of this research is the Marienthal-study by Jahoda, Lazarsfeld, and Zeisel (1933/1971) that has convincingly demonstrated that unemployment reduces rates of civic and political participation, amongst many other detrimental consequences. This finding has been corroborated in the following decades, because the unemployed exhibit strong levels of political disenchantment and disengagement. For instance, they tend to abstain from elections or support extreme - right or left-wing parties (Chabanet 2007; Coffé and Bolzendahl 2010; Verba and Nie 1972; Verba, Nie and Kim 1978; Brady, Verba and Schlozman 1995; Schur 2003). These findings seem to apply in particular to the young unemployed. [web URL: http://siba-ese.unisalento.it/index.php/paco/article/view/15 591] eng Reprinted by permission